2002
DOI: 10.2337/diacare.25.3.445
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Lifestyle Changes Are Necessary to Improve Insulin Sensitivity

Abstract: OBJECTIVE -The extent to which lifestyle must be altered to improve insulin sensitivity has not been established. This study compares the effect on insulin sensitivity of current dietary and exercise recommendations with a more intensive intervention in normoglycemic insulinresistant individuals.RESEARCH DESIGN AND METHODS -Seventy-nine normoglycemic insulinresistant (determined by the euglycemic insulin clamp) men and women were randomized to either a control group or one of two combined dietary and exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
144
1
6

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(163 citation statements)
references
References 24 publications
12
144
1
6
Order By: Relevance
“…The present study corroborates previous ones using either the CLA mixture [2][3][4][5]7,9,10,13,14,19,[30][31][32] or either one of the two main isomers 33,34 demonstrating that fasting insulin and glucose do not change during supplementation. The CLA doses in these studies ranged from 0.6 to 6.8 g/day for time periods ranging from 5 days to 2 years in healthy, overweight or obese individuals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study corroborates previous ones using either the CLA mixture [2][3][4][5]7,9,10,13,14,19,[30][31][32] or either one of the two main isomers 33,34 demonstrating that fasting insulin and glucose do not change during supplementation. The CLA doses in these studies ranged from 0.6 to 6.8 g/day for time periods ranging from 5 days to 2 years in healthy, overweight or obese individuals.…”
Section: Discussionsupporting
confidence: 92%
“…loss of 12.6 kg fat mass) to changes in any of the indices of insulin resistance. This is in accordance with a controlled trial reported by McAuley et al 34 in which normoglycemic insulin-resistant subjects were randomized either to a control group, a group with moderate dietary and exercise program or a third group with an intensive dietary and exercise program. Subjects in both intervention groups reduced total and truncal fat masses as well as waist circumference, whereas lbm was maintained.…”
Section: Discussionsupporting
confidence: 91%
“…for weight loss, adjusted for baseline, was 4.5 kg. 28 This is equivalent to an effect size of 0.66 or 0.70. Two samples of 32 have the potential to detect this difference with 80% power using the 5% level of significance.…”
Section: Methodsmentioning
confidence: 99%
“…McAuley et al placed normoglycaemic insulin-resistant adults on a diet and exercise intervention programme that included increased consumption of whole grain foods. Weight loss and enhanced insulin sensitivity using the insulin clamp technique was demonstrated on an intensive lifestyle intervention programme (McAuley et al, 2002). Chandalia et al (2000) and Giacco et al (2000) showed improved measures of glycaemic control in people with diabetes by increasing the dietary fibre content.…”
Section: Short-and Medium-term Dietary Intervention Studiesmentioning
confidence: 99%